2015
DOI: 10.1016/j.cgh.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fertilization in Women With Inflammatory Bowel Disease Is as Successful as in Women From the General Infertility Population

Abstract: BACKGROUND & AIMS Inflammatory bowel disease (IBD) affects women of reproductive age, so there are concerns about its effects on fertility. We investigated the success of in vitro fertilization (IVF) in patients with IBD compared with the general (non-IBD) IVF population. METHODS We conducted a matched retrospective cohort study of female patients with IBD who under-went IVF from 1998 through 2011 at 2 tertiary care centers. Patients were matched 4:1 to those without IBD (controls). The primary outcome was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…Earlier, the outcome of ART treatment was studied in 71 women with UC and 49 with CD from two tertiary care centres,17 18 who were compared with 470 controls from the general infertile population. It was found that the proportion of live births after the first ART cycle was similar among controls (30.2%) and patients with UC (33.8%) and CD (30.6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, the outcome of ART treatment was studied in 71 women with UC and 49 with CD from two tertiary care centres,17 18 who were compared with 470 controls from the general infertile population. It was found that the proportion of live births after the first ART cycle was similar among controls (30.2%) and patients with UC (33.8%) and CD (30.6%).…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence of the efficacy of ART treatment in patients with UC and CD. The cumulative live birth rate after six IVF cycles has only recently been described in 71 women with UC and 49 CD women and compared with patients without IBD,17 18 but the analyses did not take into account the possible effect of confounding factors which might affect fertility, such as prior surgery, comorbid disease, body mass index (BMI) and tobacco use.…”
Section: Introductionmentioning
confidence: 99%
“…The first study identified 121 female patients with IBD (UC: n = 71; CD: n = 49; unclassified: n = 1) from two tertiary IBD centers in Boston and 470 matched controls without IBD, all of whom underwent IVF between 1998 and 2011 at two affiliated centers for infertility. The study reported no differences in the cumulative rate of live births or incidence of pregnancy/live birth after the first cycle of IVF for IBD patients of either subtype compared to controls [8]. The second study described comparable rates of IVF birth rates in women with UC who underwent IPAA (n = 22) versus those with UC who had not undergone IPAA (n = 49) versus matched controls from the general infertility population [9].…”
mentioning
confidence: 94%
“…In Crohn's disease (CD), data are more equivocal regarding higher rates of infertility: voluntary childlessness (for a wide variety of reasons) may account for reported higher rates of infertility in past studies [4], although decreased ovarian reserve as measured by anti-Müllerian hormone occurs in CD, particularly at age [30 and with colonic location of disease [5,6]. Regardless of whether a woman with IBD has difficulty becoming pregnant related to surgery, disease or for other reasons, knowledge of what influences the success of in vitro fertilization (IVF) in this population as it compares to women without IBD is certainly welcome.In this issue of Digestive Diseases and Sciences, Oza et al [7] report their findings of a matched retrospective cohort study regarding specific factors associated with the success of IVF in women with IBD, a subanalysis of data derived from a larger retrospective study comparing IVF success in women with IBD relative to the general population [8]. Since this same group previously published a subanalysis examining IVF in women with UC who had undergone IPAA [9], this subanalysis is actually the third in a series that compared women with IBD undergoing IVF to the general infertility population.…”
mentioning
confidence: 99%
See 1 more Smart Citation